2019
DOI: 10.2147/cmar.s224532
|View full text |Cite
|
Sign up to set email alerts
|

<p>Transarterial Chemoembolization and Sorafenib Combined with Microwave Ablation for Advanced Primary Hepatocellular Carcinoma: A Preliminary Investigation of Safety and Efficacy</p>

Abstract: The aim of this study was to investigate the safety and efficacy of transarterial chemoembolization and sorafenib (TACE-S) combined with microwave ablation (TACE-S-MWA) for the treatment of patients with advanced primary hepatocellular carcinoma (HCC). Methods: Between January 2015 and December 2018, 152 consecutive advanced HCC patients, who underwent TACE-S-MWA (MWA group, n=77) or TACE-S (Non-MWA group, n=75), were investigated. Overall survival (OS), time to progression (TTP) and safety were compared betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Generally, as a palliative treatment, TACE cannot eliminate viable tumor cells, which may result in the failure of TACE due to local tumor recurrence and distant metastasis [120,170]. For the development and further applications of the TACE, supplemental therapeutic mechanisms, including magnetic induction hyperthermia (MIH) [145,171], microwave ablation (MWA) [172,173], high-intensity focused ultrasound (HIFU) thermotherapy [120,170,174], photothermal therapy (PTT) [175,176], and radiofrequency ablation (RFA) [177,178], etc., have been introduced to enhance the therapeutic effects. Extensive clinical studies have confirmed improved outcomes through combination therapy of TACE with interventional thermal/nonthermal ablation modalities [14,[179][180][181].…”
Section: Microspheres For Arterial Embolization Hyperthermiamentioning
confidence: 99%
“…Generally, as a palliative treatment, TACE cannot eliminate viable tumor cells, which may result in the failure of TACE due to local tumor recurrence and distant metastasis [120,170]. For the development and further applications of the TACE, supplemental therapeutic mechanisms, including magnetic induction hyperthermia (MIH) [145,171], microwave ablation (MWA) [172,173], high-intensity focused ultrasound (HIFU) thermotherapy [120,170,174], photothermal therapy (PTT) [175,176], and radiofrequency ablation (RFA) [177,178], etc., have been introduced to enhance the therapeutic effects. Extensive clinical studies have confirmed improved outcomes through combination therapy of TACE with interventional thermal/nonthermal ablation modalities [14,[179][180][181].…”
Section: Microspheres For Arterial Embolization Hyperthermiamentioning
confidence: 99%
“…Palliative ablation therapy for advanced HCC is currently under investigation. Nevertheless, combining TACE ablation and sorafenib has shown longer survival for patients with BCLC stage C [51].…”
Section: Therapies For Advanced Hccmentioning
confidence: 99%
“…The detailed characteristics of included relevant studies for this network meta-analysis were described in Table 1. which contained 8 RCTs (6,9-23) and 20 retrospective studies (10,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%